(untitled) (Conferencea, 2021)
The following article discusses the new requirements for modern education system. It suggests the integration of information technologies in the lesson in order to increase efficiency of classes. Here some of the very effective and mostly utilized methods of how to work out innovative approach and implement the technology to the learning environment.